2018
DOI: 10.3892/mmr.2018.9708
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates renal fibrosis in diabetic mice by activating the AMPK/PGC1α signaling pathway and rescuing mitochondrial function

Abstract: Mitochondrial homeostasis is a highly regulated process that serves a critical role in the maintenance of renal structure and function. The growing interest in the field of mitochondrial homeostasis promises to provide more information regarding the mechanisms involved in diabetic renal fibrosis, and aid in the development of novel strategies to combat the disease. In the present study, the effects of melatonin on renal damage in mice with diabetes were evaluated and the underlying mechanisms were investigated. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 72 publications
(84 reference statements)
4
13
0
Order By: Relevance
“…Increased production of TGF-β and activation of Smad2/3 along with an elevated expression of α-SMA, a myofibroblast marker, and fibronectin after AA injection was also significantly attenuated by melatonin, suggesting that the hormone ameliorated AA-induced fibrotic processes mainly through suppression of TGF-β/Smad signaling pathway. In line with our findings, previous studies have reported that melatonin ameliorated cyclosporine A- [34], carbon tetrachloride- [35], unilateral ureteral obstruction- [36], 5/6 nephrectomy- [13], or diabetes [15]-induced renal fibrosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increased production of TGF-β and activation of Smad2/3 along with an elevated expression of α-SMA, a myofibroblast marker, and fibronectin after AA injection was also significantly attenuated by melatonin, suggesting that the hormone ameliorated AA-induced fibrotic processes mainly through suppression of TGF-β/Smad signaling pathway. In line with our findings, previous studies have reported that melatonin ameliorated cyclosporine A- [34], carbon tetrachloride- [35], unilateral ureteral obstruction- [36], 5/6 nephrectomy- [13], or diabetes [15]-induced renal fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported that administration of exogenous melatonin ameliorated renal injury and dysfunction in pinealectomized rats [5]. It has also been shown that melatonin displays protective effects in various types of acute kidney injury (AKI) [6][7][8][9][10][11] and chronic kidney disease (CKD) [12][13][14][15]. However, the effects of melatonin on AAN have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of this hormone to reduce oxidative stress in renal mitochondria is in line to other reports in different tissues [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] which also indicate the mitochondria as a therapeutic target for the antioxidant actions of this indolamine. In summary, melatonin therapy improves overall mitochondrial dysfunction and altered mitochondrial dynamics observed in the kidney of obese diabetic condition as others reported in other conditions in renal damage [ 66 , 67 ]. Our findings reinforce a statement made by others that melatonin supplementation could be useful for improvement in stable outpatient renal transplant recipients [ 68 ].…”
Section: Discussionsupporting
confidence: 76%
“…Bleomycin-induced experimental lung fibrosis was also attenuated by treatment with melatonin [27]. In addition, melatonin has been shown to attenuate kidney fibrosis induced by CCl4 [28], unilateral ureteral obstruction [29], or diabetes [30]. Interestingly, it was also reported that melatonin ameliorated liver fibrosis induced by CCl4 [12][13][14], thioacetamide [15], or high-fat diet [16].…”
Section: Discussionmentioning
confidence: 99%